2019
DOI: 10.1108/lht-01-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

A study on users’ perception of the role of library in the sharing economic era in Korea

Abstract: Purpose The purpose of this paper is to explore the possibilities of prioritizing tasks, actual sharing of libraries, collaboration policies and the directions via quantifying the relative importance of services for each value based on users’ perceptions observed from in-depth analysis of the investigation results. Through this, the study expects that libraries will provide high – level the sharing economy services, reflecting users’ needs. Design/methodology/approach This study surveyed public library users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Creswell (2016) stated that qualitative research is a research method for investigating and understanding meanings that are considered rooted in social or humanitarian problems by several individuals or groups of people. Another opinion was expressed by Moleong (2012) who explained that qualitative research is: "research that intends to understand phenomena experienced by research subjects, for example, behavior, perceptions, motivations, actions, etc. holistically and using descriptions in the form of words and language, in a special natural context and by The characteristics of qualitative research explained by Sugiyono (2019) are as follows: "1) Carried out in natural conditions, directly to the data source and the researcher is the key instrument; 2) Qualitative research is more descriptive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Creswell (2016) stated that qualitative research is a research method for investigating and understanding meanings that are considered rooted in social or humanitarian problems by several individuals or groups of people. Another opinion was expressed by Moleong (2012) who explained that qualitative research is: "research that intends to understand phenomena experienced by research subjects, for example, behavior, perceptions, motivations, actions, etc. holistically and using descriptions in the form of words and language, in a special natural context and by The characteristics of qualitative research explained by Sugiyono (2019) are as follows: "1) Carried out in natural conditions, directly to the data source and the researcher is the key instrument; 2) Qualitative research is more descriptive.…”
Section: Methodsmentioning
confidence: 99%
“…This can form a library culture that is more dynamic, inclusive, and responsive to the needs of modern society. Studies regarding the perceptions and needs of library users can provide direction for library programs and services based on research results, and it has been found that library services can be changed according to user characteristics (Noh, et al 2019). Cooperation between libraries and information institutions includes various forms of collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…The librarians provide an essential contribution to the lending initiative, but according to the interview participants, their involvement is controversial. Public libraries are sometimes conceptualised as close cousins to the sharing economy, but the librarian's professional tradition is positioned within cultural and educational fields, with developments towards public libraries as social institutions (Hansson, 2010;Noh et al, 2019). The latter, particularly the public library's mission to promote social inclusion, is often drawn on by librarians to justify their active involvement in the daily running of BUA Kolbotn and their smooth collaboration with local volunteers.…”
Section: Bua Kolbotn: Co-production With Public Librariesmentioning
confidence: 99%
“…Experience space theory: Library experience space theory emphasizes the subjective feelings of users as the basis and aims to enhance the psychological satisfaction of users, and the experience levels, in increasing order, are: functional experience, sensory experience, emotional experience, brand experience, and design experience [31]. Nowadays, driven by new demands, human beings have entered the "heart era" of the "experience economy" to meet spiritual needs, and libraries should analyze readers' preferences for sensory experience and space selection [32,33], and improve the physical and spiritual environment to enhance readers' satisfaction with library space. To enhance patrons' perception of the beauty of library space and to enjoy the information and other services provided by the library with pleasure [34,35].…”
Section: Spatial Theory Dimensionmentioning
confidence: 99%